Clinical Practice Guidelines in Integrated Traditional Chinese and Western Medicine Rehabilitation—Cognitive Impairment - Shanli YANG; Sufang CAI; Jingyi WU; Hao CHENG; Ye HUA; Xinmei ZHANG; Weijia LIN; Wenliang YANG (康复学报)
Post-stroke cognitive impairment (PSCI) refers to a series of syndromes that meet the diagnostic criteria of cognitive impairment 6 months after stroke. PSCI seriously affects patients'ability of daily life activities and quality of life, hinders the comprehensive rehabilitation of stroke patients, and brings heavy burden to society and families. The clinical practice guidelines of PSCI rehabilitation based on evidence-based medicine are of great significance to standardize clinical diagnosis and treatment and optimize the clinical effects. The guidelines focus on the development of traditional Chinese medicine (TCM) standards of PSCI, give full play to the advantages of TCM, and devote themselves to the development of integrated traditional Chinese and western medicine rehabilitation measures to optimize the outcome of rehabilitation, so as to provide certain reference basis for the formulation of integrated traditional Chinese and western medicine diagnosis and treatment strategies for cognitive rehabilitation. The guidelines regulate PSCI in terms of terminology and definitions, clinical diagnostic criteria, rehabilitation evaluation criteria, rehabilitation treatment, etc., aiming to help clinicians and therapists determine the optimal intervention measures, synthesize relevant information, and maximize clinical efficacy. The guidelines consist of traditional rehabilitation, western rehabilitation and rehabilitation treatment of integrated traditional Chinese and western medicine, which explain concrete practice content and levels of evidence of various methods. The guidelines are of importance for scientific, systematic, validity and clinical applicability.